European singles and doubles badminton matches analysis with specific focus on pair doubles - Le Mansec, Y.; Boiveau, M.; Doron, J.; Jubeau, M. (International Journal of Racket Sports Science, 2023)
The main aims of the present study were i) to examine the different demands (temporal and muscular data) between different types of events in badminton (part 1) and ii) to compare the real activity (areas distribution and strokes distribution) between the two players who composed the pair during the three types of doubles that occur in badminton (part 2). Seven matches were analyzed for both men`s and women`s singles and for men`s, women`s and mixed doubles during the 2016 European Championships. In Part 1, both timing structure (match duration, number of points, rally duration, rest time, effective playing time and shot frequency) and specific movements (jumps and lunges) were compared between the five types of events. In Part 2, after dividing the court into four zones, we compared the activity of the two players within the same pair in each of these zones. The distribution of technical variables and specific movements was also analysed. For Part 1, male and mixed doubles showed the shortest rally duration (~-45%), the longest rest between two rallies (~+18%), as well as the highest shot frequency (~+24%) when compared to male and female singles and female doubles. Male and female singles showed the highest number of jumps (+40% when compared to doubles) and lunges (+250% when compared to doubles). Male and female singles showed the highest number of jumps (+40% when compared to doubles) and lunges (+250% when compared to doubles). For Part 2, we observed that spatial and notational distribution between players of the pair is largely dependent on the type of double considered. This study demonstrated that the constraints of a badminton game are specific and related to the type of event played (males or females and/or singles or doubles).